A dynamic and cyclical model of bounded ethicality. (2016) - Chugh, Dolly; Kern, Mary C.
Abstract: We introduce a new model of bounded ethicality which helps explain three persistent puzzles of ethical behavior: when moral awareness is or is not present, when ethical behavior is more or less consistent with past behavior, and when blind spots obscure our ethical failures. The original conception of bounded ethicality (Chugh, Banaji, & Bazerman, 2005 ) described the systematic psychological constraints on ethical behavior and has contributed to our field's understanding of the phenomena of everyday, "ordinary" unethical behavior. In this more detailed model, we delineate these systematic processes and mechanisms and show how concepts of automaticity, self-view, and self-threat play critical roles in our ethical decision-making. The model describes distinct, asymmetric patterns of (un)ethical behavior and pinpoints the contingency which determines which pattern is more likely to unfold, including when we will trend to more or less automaticity and more or less ethical behavior. Our model integrates and synthesizes many of the key models and findings in recent behavioral ethics research into a single, overarching model of ethical decision-making, offering an anchor for new questions and a new realm of study.